A new biofeedback approach for the control of awake bruxism and chronic migraine headache: utilization of an awake posterior interocclusal device - HAGGIAG, Alain; SPECIALI, José Geraldo (Arquivos de Neuro-Psiquiatria, 2020)
Background: The relationship of bidirectional comorbidity between chronic migraine and pain in the cephalic segment led us to evaluate the improvement in reducing the pain in patients diagnosed with chronic migraine headache and awake bruxism, when undergoing treatment with a partial posterior interocclusal device designed for the management and control of awake bruxism through biofeedback. Methods: Seventy-four patients were evaluated during the following periods: pretreatment, seven, thirty, ninety, one hundred and eighty days, and one year. The evaluation was carried out by measuring the pain in the pretreatment period and pain reduction after awake bruxism treatment, using clinical evaluation and numerical scales for pain. Results: Most of the patients who complained of headache migraine pain, masticatory myofascial pain, temporomandibular joint and neck pain experienced a significant reduction in overall pain, including headaches, between t0 and t30 (p<0.0001). After 30 days of using the device, it was observed that the improvement remained at the same level without any recurrence of pain up to t90. At t180 and t360, it was observed that even with the device withdrawal (at t90) the improvement remained at the same level. Conclusion: The utilization of a posterior interocclusal device designed for the management and control of awake bruxism through biofeedback seems to contribute to the reduction of pain (including migraine headache) in the majority of patients, and, even with the device withdrawal (at t90), the improvement remained at the same level, suggesting the patients succeeded in controlling their awake bruxism and consequently the pains.
Keywords: Bruxism; Facial Pain; Occlusal Splints; Biofeedback, Psychology; Migraine Disorders.